Penetapan Kadar Kalsium Laktat dengan Menggunakan Metode Titrasi Kompleksometri - Nur Khadijah Anasyah; Nurfadillah Nurfadillah; Dian Fadillah; Rini Ariyanti; Musfirah Musfirah; Putri Indah Ramadhani; Amri Alwi; Yuniarsyah Yuniarsyah; Rismawati Kalean; Sulfiana Sulfiana; Yuyun Sri Wahyuni; Masyhuri Muhaimin; Haryanto Haryanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research aims to determine calcium lactate levels using the complexometric titration method, which involves the formation of a complex between metal ions and ligands, specifically using EDTA (Ethylenediaminetetraacetate) as a titrant. The sample was dissolved in distilled water, the murexide indicator was added, and titrated with complexon III solution until the color changed from orange to violet as a marker for the end point of the titration. Data analysis shows that the percentage of calcium lactate levels in replication (1) is 93.32%, replication (2) 101.60%, replication (3) 95.93%, replication (4) 103.78%, replication (5) 109.02%, replication (6) 87.87%, replication (7) 95.93% and replication (8) 100.95%, and the percentage obtained the average purity is 98.55%. However, replications 5 and 6 did not comply with the standards of the Indonesian Pharmacopoeia VI edition (94.0–106.0%). This research shows that the complexometric titration method is effective in determining calcium lactate levels with good accuracy, as long as it is carried out with appropriate procedures and strict control of the analysis conditions.